Pharmaceutical care in digital revolution : insights towards circular innovation - Rijcken, Claudia (Academic Press, an imprint of Elsevier, 2019)
Pharmaceutical Care in Digital Revolution demonstrates how blending human and digital pharmaceutical care can establish optimal Apothecary Intelligence (AI). Organized into four parts, it examines digital health advances that will synergize the pharmaceutical care process and prepares stakeholders for a dynamic future, fueled with innovation. Beginning with the global picture on health care systems, patients' expectations, and current pharmaceutical care practices, the book covers details of relevant digital technologies as well as compliance, ethical, educational, and cultural aspects to take successful steps towards digital pharmaceutical care. The text includes links to lectures and technology facts, tutorials on how to implement advances in your own working environment, and examples of stakeholders who are successful in building synergy between digital and pharma. Pharmaceutical Care in Digital Revolution is a practical resource to equip pharmaceutical care stakeholders, such as pharmacists, physicians, pharmacy technicians, and students as well as those in surrounding ecosystems like payers or regulators. It is a crucial reference to understand how technological innovation is changing the paradigm in which we provide current and future pharmaceutical care and how to keep it accessible, affordable, and sustainable.